Two new species of Ascochyta from India - KAMAL2, A. N. RAI1 AND (Indian Phytopathology, 2002)
Two new species, A. bombacacearum .and A. poacearum, are described and illustrated on plants of Bombax ceiba and Saccharum munja respectively.